In-hospital invasive strategy and outcomes in non-ST elevation acute coronary syndrome management from Thai acute coronary syndrome registry - Arintaya Phrommintikul (2018)
Background: The management guideline of acute coronary syndrome has been changed in recent years, especially in the group of non-ST elevation acute coronary syndrome (NSTE-ACS). Presently, there is no existing guideline in Thailand. Additionally, several different management factors of health care from Western countries being used. Objective: Evaluate the real management strategy, including the utilization of invasive management and pharmacotherapy of NSTE-ACS Thai patients in the absence of official clinical management guideline. Material and Method: Thai Acute Coronary Syndrome (Thai ACS) Registry is a large, observational prospective, population-based registry designed to collect the data of "real-life" patient management. The full details of methods have been published in the present supplement. Results: Five thousand five hundred and thirty-seven consecutive patients were registered between August 1, 2002 and July 31, 2005. Among these patients, 3,548 (64.1%) were diagnosed with non-ST elevation myocardial infarction (NSTEMI) and 1,989 (35.9%) with unstable angina. Coronary angiography was performed during hospitalization in 2,476 patients (44.7%). From 2,476 patients who underwent coronary angiogram, 405 (16.4%) had revascularization within 2 days and 1,019 (42.9%) after 2 days. Overall, in-hospital mortality was 9.5% and cardiac mortality was 6.3%. Patients with NSTEMI had more than 4 times the mortality of patients with unstable angina (13.1 vs. 3.0%, p < 0.001). Patients who received only medical treatment without coronary angiogram had the highest mortality rate. The in-hospital outcomes were not different between patients who received early or delayed revascularization. Conclusion: Mortality rate of NSTEACS in the authors' registry was very high. NSTEMI had the worse prognosis. Invasive strategy is associated with better in-hospital outcome but is underutilized.